THE SPECIFICITY OF DEICTIC UNITS IN ENGLISH IN INTERNATIONAL POLITICAL SPEECHES (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article investigates the linguistic and pragmatic functions of deictic units in English as used in international political speeches. Deixis, as a core feature of language and communication, plays a crucial role in shaping the relationship between political leaders and their audiences. The study explores how personal, spatial, and temporal deixis contribute to establishing authority, creating inclusivity, and reinforcing ideological positions within global political discourse. By analyzing the linguistic features and pragmatic intentions behind the use of deictic expressions such as “we,” “you,” “here,” and “now,” the research reveals how political figures strategically manipulate deixis to align with audiences, construct social reality, and legitimize power. The findings highlight that deictic units in political speeches go beyond reference; they are vital tools for constructing identity, perspective, and shared context in the international arena.